Inexpensive Immersive Projection - Yuen, Nancy P. Y.; Thibault, William C. (2008 IEEE Virtual Reality Conference, 2008)
Most projector-based immersive displays have numerous problems relating to complexity, space, and cost. We present a technique for rendering perspectively correct images using a casual arrangement of a projector, a mirror and a display surface. Our technique renders an arbitrarily wide field of view using an efficient GPU-based single-pass rendering algorithm. The rendering algorithm is preceded by a one-time camera-based geometric correction calibration step. As we will describe, this technique can be implemented with inexpensive, commodity hardware and using readily available display surfaces. Thus, this technique enables immersive projection systems to be used in casual locations, such as a classroom or even in the home.